A Study on Future City Models through Domestic and Foreign Cases -Focusing on the Zero-energy Town and Smart City- - Kim, Jeongmin; Lee, Kwangjin; Kim, Yongseong (International Journal of Engineering and Technology, 2019)
Recent increases in population, carbon emission, and energy consumption have led to the placement of greater emphasis on the application and development of new and renewable energy technologies and the securing of alternative fuels. In light of this, several institutions in South Korea have undertaken preliminary studies that include literature reviews and case studies related to smart cities and the development of zero-energy complexes as solutions to these issues. However, these studies in most instances are non-comprehensive and focused on specific cases. Several cities in South Korea lack adequate preparations to realize future cities. In light of this, through the study of domestic and foreign cases regarding smart cities and the concept of zero-energy towns, new and renewable energy and ICT technology applications centered on methods of realizing future cities were analyzed and in doing so, basic materials necessary for the effective realization of future cities in South Korea were established.Â Â